Why students take elective business ethics courses: Applying the theory of planned behavior - Randall, Donna M. (Journal of business ethics, 1994)
Despite the prevalence of elective business ethics courses, little research has sought to explain and predict why some students enroll in these courses and while others do not. Using the theory of planned behavior (Ajzen and Madden, 1986) as a theoretical foundation, 178 graduate students in Ireland were surveyed about their intention to sign up for an elective ethics class. Their behavior was measured two months later. The results reveal the power of the theory of planned behavior to explain and predict who takes elective ethics classes.